Innovation in construction : an international review of public policies / edited by Andre Manseau. - Manseau, Andre (E.&F.N. Spon, 2001)
How can innovation in the construction industry be strengthened? This book presents a framework for the analysis of innovation models and systems in construction and an international comparison of these systems.